Ecological Predictors of Perceiving Scarcity in Childhood (2017)
Evidence from multiple disciplines suggests there is a strong association between poverty and child development, mediated by worry and stress. Nevertheless, it is yet unclear why some children worry more about their family economic situation while others do not. In this paper, we analyze ecological predictors of worrying for family money in childhood. For this purpose, we use the second wave of the International Survey of Children's Well-being (ISCWeB), in which children from 16 developed and developing countries stated whether they worry about their family money. The dataset also contains rich information about individual characteristics, such as age and gender, and contextual factors, such as home and family life, neighborhood quality, school life, and peers relationship. Using descriptive analysis and ordered probit models, we find that family relationship quality, school climate, and peer involvement are the main predictors of perceiving scarcity in childhood, even after controlling for other individual characteristics and heterogeneity across countries